The evaluation of teaching and learning methods in geriatric dentistry at two public health colleges in Thailand - Losupakarn, Rattanun; Ngoenwiwatkul, Yaowaluk; Kettratad, Matana (Thai Dental Public Health Journal, 2022)
Dental nurses play an important role in primary oral health care for older adults living in the community. The development of a geriatric dental curriculum for dental nurses is an essential part of preparing the workforce for Thailand toward aged society. Amid the COVID-19 pandemic, social distancing and lockdowns have posed challenges in organizing classroom learning from traditional learning to online learning. This study aimed at evaluating the effectiveness of teaching and learning platforms in the geriatric dental classrooms for dental nurse students. The study employed quasi-experimental research to compare an online geriatric dental classroom (the intervention group, n = 31) with a project-based geriatric onsite dental classroom (the comparison group, n = 31). The instruments in this study were pre- and post-knowledge tests, pre- and post-affective domain assessments, and a course satisfaction questionnaire. Comparisons of data between two groups using independent sample t-test and independent samples Mann-Whitney U test at the 0.05 level of significance. This study found that there was no statistical difference toward the knowledge of both groups, while there was a statistical difference in self-efficacy and ageism scale in affective domain assessments (p < 0.05). The course satisfaction in the intervention group was significantly higher than that of the comparison group (p < 0.01). In conclusion, amid the COVID-19 pandemic, an online geriatric dental classroom may substitute the traditional geriatric dental classroom in terms of improving the cognitive and affective domains. Moreover, students in an online geriatric dental classroom are satisfied with their online classroom.